2019
DOI: 10.1155/2019/2502908
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Rheological Properties of Egg Albumin Foams Are Affected by Ionic Strength and Basil Seed Gum Supplementation

Abstract: In this study, the effect of ionic strength and basil seed gum (BSG) on the foaming properties of egg white albumin (EWA) was studied. The foam was prepared with 1% EWA (w/v) in the presence of different concentrations of sodium chloride (NaCl; 0, 0.5, and 1% w/v) and BSG (0, 0.1, and 0.3% w/v). The results showed that foam density and foam stability of EWA significantly (p<0.05) increased with an increase in BSG concentration (from 0 to 0.3% w/v). On the contrary, an increase in NaCl concentration (from 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This test shows the effect of different rates of strain/stress on the viscoelastic behaviors of the cheeses. Elastic modulus ( G ′) and viscous modulus ( G ″) are measured dynamically, and they are, respectively, elastic and viscous behavior (Razi, Motamedzadegan, Shahidi, & Rashidinejad, ; Tunick, ). In this study G ′ > G ″, the elastic component dominates to the viscoelasticity for all treatments at any period of storage, this indicated that all cheese samples had a solid‐like behavior and own dense structure.…”
Section: Resultsmentioning
confidence: 99%
“…This test shows the effect of different rates of strain/stress on the viscoelastic behaviors of the cheeses. Elastic modulus ( G ′) and viscous modulus ( G ″) are measured dynamically, and they are, respectively, elastic and viscous behavior (Razi, Motamedzadegan, Shahidi, & Rashidinejad, ; Tunick, ). In this study G ′ > G ″, the elastic component dominates to the viscoelasticity for all treatments at any period of storage, this indicated that all cheese samples had a solid‐like behavior and own dense structure.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the powder density, 2 g of it was poured into a 50-mL graduated cylinder and the volume of this powder was recorded (Razi et al, 2019). Foam density was calculated by dividing the weight by the volume of the foam according to the following formula;…”
Section: Densitymentioning
confidence: 99%
“…As the concentration of basil seed gum increased, the density and foam stability of the OVA foam increased, while the expansion rate of the foam decreased. The increased foam stability was attributed to the interaction of protein and polysaccharides that can improve the stability of the interface layer, which can produce more stable foam to prevent coalescence of bubbles (Razi et al., 2019). These results indicated that hydrocolloids improved foaming performance mainly by increasing viscosity, stabilizing the air–water interface, and promoting interaction with proteins.…”
Section: Effect Of Polysaccharides On the Functional Properties Of Ewpmentioning
confidence: 99%
“…Polysaccharides improved the foaming property of proteins not only via their inherent properties, but also closely related to external factors, including pH, temperature, and ionic strength (Razi et al., 2019). At pH 3, the stability of EWP foam was poor, and polysaccharides greatly improved the stability of foam (Miquelim et al., 2010; van den Berg et al., 2015), because the lower protein repulsive force enhanced the interaction between air and water at the interface, forming a more stable and firm protein membrane (Kuropatwa et al., 2009).…”
Section: Effect Of Polysaccharides On the Functional Properties Of Ewpmentioning
confidence: 99%